ANALISIS WACANA PADA PIDATO BARRACK OBAMA â€œLEGALIZATION OF SAME â€“ SEX MARRIAGEâ€ - Talu, Verawati Agnes (JURNAL ELEKTRONIK FAKULTAS SASTRA UNIVERSITAS SAM RATULANGI, 2016)
ABSTRACT This skripsi was done as a requirement to obtain bachelor Degree in English Department in Sam Ratulangi University. This research is entitled â€œDiscourse Analysis on President Barrack Obamaâ€™s Speech â€˜Legalization of Same-Sex Marriageâ€™ â€. It is an attempt to analyze and explain the discourse analysis norms in Barrack Obama speech. There are three steps to finish this research. First step is preparation, the writer reads some books, internet sites, and other references about language, linguistic, and discourse analysis to find out the characteristics of data and theory which are relevant to the topics in this study. Second step is data collection, the writer take Barrack Obamaâ€™s speech on the internet and reads it for several times a day to have a deep understanding of the manuscript. Third step is data analysis, the collected data will be identified, classified, and analyzed based on the theory of Alba-Juez. The result of this research show that in cohesionÂ  there are 77 pronouns, 4 subtitusion, no ellipsis, 21 conjuction and 14 lexical. The theory is taken from Alba-Juez (2008:20) for seven normsÂ  and supported the theory by De Beaugrande & Dressler (1986:8) and Aarts and Aarts (1982:4). Â  Keywords: Discourse Analysis, Barrack Obama Speech